PENGARUH FRAUD HEXAGON TERHADAP FRAUDULENT FINANCIAL STATEMENT - Maulina, Neneng Sherly; Meini, Zumratul (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2023)
ABSTRACTFraudulent financial statements are actions that are carried out in a planned manner that harm other parties by presenting incorrect financial information. This research aims to analyze the influence of the fraud hexagon theory, that measured with financial stability, external pressure, financial target, state owned enterprises, ineffective monitoring, and frequent number of CEO’s picture on fraudulent financial statement, empirical study on companies listed on the IDX for the period 2017 – 2021. This research contributes by considering more conditions that affect the possibility of fraud. The number of data samples in this study were 81 manufacturing companies and the total number of observations was 405. This study used Logistic Regression analysis which was processed using SPSS V25. The results of this study indicate that external pressure, state owned enterprises, and frequent number of CEO’s picture has a positive effect on fraudulent financial statement, while financial stability, financial target, and ineffective monitoring does not have effect on fraudulent financial statement. It is hoped that the company will further improve the control of the company, especially in dealing with fraud in financial statements based on the fraud hexagon theory.Keywords: Fraud, Fraud Hexagon, Fraudulent Financial StatementABSTRAKFraudulent financial statement merupakan perbuatan yang dilakukan secara terencana yang merugikan pihak lain dengan cara menyajikan informasi keuangan yang salah. Penelitian ini bertujuan untuk menganalisis pengaruh teori fraud hexagon, dengan menggunakan pengukuran financial stability, external pressure, financial target, state owned enterprises, ineffective monitoring, dan frequent number of CEO’s picture terhadap fraudulent financial statement, studi empiris pada perusahaan yang terdaftar di BEI periode 2017 – 2021. Penelitian ini memberi kontribusi dengan mempertimbangkan lebih banyak kondisi yang mempengaruhi kemungkinan terjadinya kecurangan. Jumlah sampel data pada penelitian ini adalah 81 perusahaan manufaktur dan jumlah total observasi 405. Penelitian ini menggunakan analisis Regresi Logistik yang diolah menggunakan SPSS V25. Hasil penelitian ini menunjukan bahwa kondisi external pressure, state owned enterprises, dan frequent number of CEO’s picture berpengaruh positif terhadap peluang terjadinya kecurangan laporan keuangan. Sedangkan financial stability, financial target, dan ineffective monitoring tidak berpengaruh terhadap fraudulent financial statement. Diharapkan perusahaan untuk lebih meningkatkan pengendalian/kontrol mereka terutama dalam mengatasi kecurangan dalam laporan keuangan berdasarkan teori fraud hexagon.Kata Kunci: Fraud, Fraud Hexagon, Kecurangan Laporan Keuangan